If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4g + -3g(5 + -2h) = 0 4g + (5 * -3g + -2h * -3g) = 0 4g + (-15g + 6gh) = 0 Combine like terms: 4g + -15g = -11g -11g + 6gh = 0 Solving -11g + 6gh = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'g'. g(-11 + 6h) = 0Subproblem 1
Set the factor 'g' equal to zero and attempt to solve: Simplifying g = 0 Solving g = 0 Move all terms containing g to the left, all other terms to the right. Simplifying g = 0Subproblem 2
Set the factor '(-11 + 6h)' equal to zero and attempt to solve: Simplifying -11 + 6h = 0 Solving -11 + 6h = 0 Move all terms containing g to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 6h = 0 + 11 Combine like terms: -11 + 11 = 0 0 + 6h = 0 + 11 6h = 0 + 11 Combine like terms: 0 + 11 = 11 6h = 11 Add '-6h' to each side of the equation. 6h + -6h = 11 + -6h Combine like terms: 6h + -6h = 0 0 = 11 + -6h Simplifying 0 = 11 + -6h The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
g = {0}
| 133+94+x=180 | | (2x^2)+m*x+5*m=0 | | .75w-5=.25w-1 | | 133+94+x=360 | | x^2-14x-49=4 | | 6x^4-x^2=35 | | (9,9)(13,9)= | | -6(9-4)= | | 2.5v-4=3.5v | | -45=-18x-70 | | a+8=9 | | 0.95y=0.55y+60 | | 11=g+6 | | -7*-7= | | 2(m-5)+4=56 | | x-2x=41/2 | | 3x=-y+7 | | .83t+4=.16t-2 | | 11-8x=9x-7x-19 | | -2(5w-5)+6w=5(w+5) | | 9+4y=98 | | 32+5=13 | | 500-133x=500 | | 9x*-4*4= | | 10x^2-41x+32=0 | | 5m^2+60m+163=3 | | 56+90+x=180 | | 4x^2-60x-400=0 | | g(x)=x^2+10x | | 3(w-6)-6=-6(-3w+2)-6w | | 5(4x-4)=8x+28 | | (4v+9)(1-V)=0 |